2003
DOI: 10.1074/jbc.m301489200
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Analysis of Cytochromes P450 2C2 and 2E1 Molecular Interactions in Living Cells

Abstract: The molecular organization of microsomal cytochromes P450 (P450s) and formation of complexes with P450 reductase have been studied previously with isolated proteins and in reconstituted systems. Although these studies demonstrated that some P450s oligomerize in vitro, neither oligomerization nor interactions of P450 with P450 reductase have been studied in living cells. Here we have used fluorescence resonance energy transfer (FRET) to study P450 oligomerization and binding to P450 reductase in live transfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 39 publications
4
68
0
Order By: Relevance
“…A similar mechanism may also take place in the membrane, where microsomal cytochromes P450 are also known to exist in equilibrium between monomers and oligomers [67][68][69][70][71][72]. However, the reversibility of oligomerization in the membrane, as opposed to virtual irreversibility in solution, would blunt the manifestations of the proposed conformational heterogeneity in the membrane-bound enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism may also take place in the membrane, where microsomal cytochromes P450 are also known to exist in equilibrium between monomers and oligomers [67][68][69][70][71][72]. However, the reversibility of oligomerization in the membrane, as opposed to virtual irreversibility in solution, would blunt the manifestations of the proposed conformational heterogeneity in the membrane-bound enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2E1 was shown to exist as a 10-mer in solution that could not be dissociated by high concentrations of detergent (42). Szczesna-Skorupa et al (43) showed that CYP2E1 does not self-associate as measured by fluorescence resonance energy transfer (FRET) in cell culture, although CYP2E1 was shown to complex with reductase. In contrast, homomeric complex formation was reported for CYP2C2 using this technique (43).…”
Section: Discussionmentioning
confidence: 99%
“…Szczesna-Skorupa et al (43) showed that CYP2E1 does not self-associate as measured by fluorescence resonance energy transfer (FRET) in cell culture, although CYP2E1 was shown to complex with reductase. In contrast, homomeric complex formation was reported for CYP2C2 using this technique (43). Again, complex formation between CYP2C2 and reductase was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This functional heterogeneity appears to be linked closely to the oligomeric state of the enzyme [19,20]. Microsomal cytochromes P450 are known to form oligomers both in solution [25][26][27] and in membranes [28][29][30][31][32][33], and direct association between P450s has been recognized as an important determinant of function [34][35][36][37]. In particular, functional heterogeneity of a single P450 species caused by oligomerization has been revealed in interactions with substrates [19,38,39].…”
Section: Introductionmentioning
confidence: 99%